Electoral Programs: Theory and Relevance in the Electoral Contest - Ramírez Franco, Luz Dary (Revista del CLAD Reforma y Democracia, 2018)
AbstractIn order to demonstrate the relevance of electoral programs as an object of study to test electoral competition, representation, the positioning of the parties and other theoretical sections of political science, this article presents a theoretical review of the sources that support them. Also, the Manifesto Research on Political Representation (MARPOR) database methodology is outlined as one of the tools that has allowed to contrast and validate this theoretical body. The paper also presents a section on the general characteristics of the electoral programs. Both theoretical and empirical studies lead to conclude that electoral program is so relevant in the field of electoral competition that it should be defined as a political contract between candidates/party and voters, and that this role should be understood as a first step to give this document a legal character, not without mentioning the need to institutionalize an ex-ante and ex-post evaluation of it.
Keywords: Election; Electoral Systems; Representation; Political Party